KECENDRUNGAN FAKTOR-FAKTOR YANG MEMPENGARUHI WISATAWAN MANCA NEGARA DALAM MEMBELI PAKET WISATA PADA BIRO PERJALANAN DI KODYA DENPASAR PROVINSI BALI - I WAYAN PANTIYASA (Jurnal Ilmiah Hospitality Management, 2010)
The development of a travel bureau as one component of the Bali Tourism is growing very rapidly, causing a very tight competition between companies tersebut.Penelitian Travel Bureau aims to provide information to the Company, Travel Bureau tour of the trend factors that affect foreign tourists buying package tour.dari The research concludes that factors - factors that influence trends of foreign tourists buy a package tour, the biggest factor for competitive advantage and other factors: tourist attraction, motivation, competence, service, value added, information security, technology, personalities. From the results of this study is expected to entrepreneurs in arranging tour packages should be able to pay attention to these factors.